Hyperbaric Prilocaine Versus Hyperbaric Bupivacaine for Spinal Anesthesia in Women Undergoing Elective Cesarean Section: A Comparative Rrandomized Double-blind Study. Issue 2 (24th June 2022) - Chapron, K.; Sleth, J.C.; Capdevila, X.; Bringuier, S.; Dadure, C.
Abstract : ( Anaesthesia . 2021;76:777–784. [Epub January 11, 2021]) Spinal anesthesia is the standard technique for patients undergoing cesarean delivery (CD). Bupivacaine has been a mainstay for spinal anesthesia for decades due to its minimal onset time and extended duration of motor and sensory block. There are disadvantages, however, such as some effect variability between patients. Prilocaine is a newer local anesthetic and is expected to provide a shorter duration of motor block. The aim of this study is to compare the motor block durations of hyperbaric prilocaine and bupivacaine when used for spinal anesthesia in patients undergoing elective CD.